First Report of the International Serial Transverse Enteroplasty Data Registry: Indications, Efficacy, and Complications - Modi, Biren P (2007)
BACKGROUND: Serial transverse enteroplasty (STEP) is a novel surgical therapy for short bowel syndrome and is being used with increasing frequency worldwide. Because no single center is likely to obtain sufficient experience for meaningful analysis, we created the International STEP Data Registry to allow for larger, multicenter patient accrual and followup. This report describes patient characteristics, operative parameters, and early results of STEP in the first 38 patients enrolled in the International STEP Data Registry. STUDY DESIGN: After IRB approval, data were entered online through password-protected enrollment and followup forms. Patient and procedural characteristics were analyzed. Pre- and postoperative small bowel length and enteral feeding tolerance were compared with the paired t-test. RESULTS: Between September 1, 2004, and April 30, 2006, 19 centers from 3 countries enrolled 38 patients. Median followup from STEP procedure to analysis was 12.6 months (range 0 to 66.9 months). Indications for STEP were short bowel syndrome (SBS, n = 29), bacterial overgrowth (n = 6), and neonatal atresia (n = 3). Mean small intestine length was substantially increased in all groups (68 ± 44 cm versus 115 ± 87 cm, p < 0.0001, n = 27). Notable complications included intraoperative staple line leak (n = 2), bowel obstruction (n = 2), and fluid collection or abscess (n = 3). Late outcomes included progression to transplantation (n = 3) and mortality (n = 3). For the short bowel syndrome cohort, enteral tolerance was notably increased from 31% ± 31% to 67% ± 37% of calories (p < 0.01, n = 21). CONCLUSIONS: STEP has been performed at multiple centers with minimal complications and encouraging outcomes. Indications for the procedure have broadened beyond short bowel syndrome to include bacterial overgrowth and neonatal intestinal obstruction with dilated proximal intestine. Continued accrual and followup of patients in the International STEP Data Registry will elucidate the longterm safety and efficacy of the procedure, with the goal of improved patient selection and operative timing.